EFEKTIVITAS KOMUNIKASI BUDAYA KEBUN DALAM PENINGKATAN KENYAMANAN KERJA DI PERKEBUNAN SUMATERA - Riadi, Selamat; Hasibuan, Hasrul Azwar (Jurnal Ilmiah Al-Hadi; Vol 4 No 2: Juli 2018DO - 10.54248/alhadi.v4i2.747, 2020)
Communication of plantation employees can be seen from the comfort of work in the form of internal and external closeness to the leader. Employee Communication is the goal of a close relationship between employees and leaders and between employees themselves, the synergy of communication is a clear standard and can be universally accepted, Employees of Garden Employees and Garden Culture are routines of how to use the time a little can explain the work. This problem can have an impact on socio-cultural aspects to refer to performance issues. The ability of approach and motivation must be able to be carried out by an assistant, both the ability of dialogue, humility, trust, hope and critical thinking, in order to provide harmony in plantation companies.